2016
DOI: 10.1007/s10815-015-0640-x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of the effects of postponing motherhood among hospital gynecologists: is their knowledge sufficient to offer appropriate help to patients?

Abstract: Overall, the survey clearly showed that the knowledge of hospital gynecologists about the effects of age on woman's fertility and ART effectiveness is largely insufficient to offer scientifically correct, helpful information to patients. Properly targeted corrections to academic and periodical educational programs for Ob/Gyn specialists are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Other studies confirmed the poor fertility knowledge and fertility awareness among people of reproductive age in the United States, Sweden, Germany, Italy, Japan and other countries [9][10][11][12][13][14][15]. In addition, some studies have demonstrated that some professionals, including obstetrics and gynaecology resident physicians and nurses, tend to underestimate age-related fertility decline and overestimate the success rate of fertility treatments [16][17][18][19]. Compared with Western countries, fertility knowledge is relatively less documented in Asia.…”
Section: Introductionmentioning
confidence: 85%
“…Other studies confirmed the poor fertility knowledge and fertility awareness among people of reproductive age in the United States, Sweden, Germany, Italy, Japan and other countries [9][10][11][12][13][14][15]. In addition, some studies have demonstrated that some professionals, including obstetrics and gynaecology resident physicians and nurses, tend to underestimate age-related fertility decline and overestimate the success rate of fertility treatments [16][17][18][19]. Compared with Western countries, fertility knowledge is relatively less documented in Asia.…”
Section: Introductionmentioning
confidence: 85%
“…Our findings may help decision-makers and practitioners implement measures to mitigate the risk of low-prognosis and optimize reproductive planning. Awareness campaigns highlighting the adverse impact of advanced female age and impaired ovarian reserve on reproductive success ( 35 , 36 ), the effect of lifestyle changes ( 37 – 40 ), and the role of treatment strategies to improve treatment success could be explored ( 41 46 ). Although the impact of the above interventions on POSEIDON prevalence rates remains mostly unknown, our data suggest that the “low-prognosis” burden could be prevented at least partially by treating patients earlier.…”
Section: Discussionmentioning
confidence: 99%
“…When asked to estimate the livebirth rate following one IVF treatment, initiators and non-initiators did not differ significantly, and both groups vastly overestimated the overall probability of a live birth. While studies have found that patients in the general population falsely believe that IVF is more successful than it is ( Wyndham et al, 2012 ), more recent studies have also found that practising gynaecologists and OB/GYN residents report similar misconceptions ( Garcia et al, 2017 , Revelli et al, 2016 ). The livebirth rate for women undergoing IVF varies considerably throughout the world, with rates at 20% in Latin America and Canada, 20–25% in Europe, and 27–29% in the USA ( Centers for Disease Control and Prevention (CDC) et al, 2014 ; Kushnir et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%